The late works of Hayao Miyazaki : a critical study, 2004-2013 - Cavallaro, Dani, 1962- (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2015)
"Once a favorite of mainly art house audiences, Hayao Miyazaki's films have enjoyed increasing exposure in the West since his Spirited Away won the Oscar for Best Animated Feature in 2003. The award signaled a turning point for Miyazaki's Studio Ghibli, bringing his films prominence in the media and driving their distribution in multiple formats"--
Hayao Miyazaki: past and present -- A "war love story": Howl's Moving Castle (2004) -- "life is a wave on the sea": tales from Earthsea (2006) -- "The ocean as a living presence": Ponyo (2008) -- "The courage to live": The secret world of Arrietty (2010) -- "Destroy the old and you destroy our memory of the past": From up on Poppy Hill (2011) -- "We must try to live": The wind rises (2013) -- Filmography.
Also issued online.
boek
Keywords: Miyazaki, Hayao, -- 1941- -- Criticism and interpretation; Animation (Cinematography) -- Japan